POTENSI FITRAH DALAM DIRI MANUSIA - Muchammad Rozzaq Auwali; Muhammad Habib al-Anshari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to explain the Islamic perspective on human fitrah (innate disposition) and its implications within the context of Islamic education. As the most noble of creations, humans are endowed with fundamental potentials (fitrah) encompassing physical, intellectual, and spiritual aspects that must be optimally actualized. The research method employed is a literature review (library research) with a descriptive qualitative approach. Data were collected through documentation techniques from various relevant literatures, including books and scientific articles. The results indicate that human potential consists of four main dimensions: instinctive (emotional), sensory (physical), intellectual, and religious (spiritual) potentials. In the Islamic perspective, humans are born in a state of purity (fitrah) and carry an innate inclination toward monotheism (tawhid). Although born without actual knowledge, humans are equipped with tools such as the senses, reason, and heart to acquire knowledge from their environment. This concept of fitrah has direct implications for Islamic education, where education serves as a means to develop these potentials so that humans can fulfill their mission as servants of Allah ('abd) and vicegerents on earth (khalifah). Islamic education must be directed toward preserving the purity of fitrah and guiding human intellectual, social, and aesthetic potentials toward worldly prosperity and happiness in the hereafter. In conclusion, a comprehensive understanding of fitrah serves as the theoretical foundation that determines the direction, methods, and goals of effective Islamic education.